KINERJA GURU TERHADAP MOTIVASI BELAJAR SISWA MADRASAH ALIYAH KEPENUHAN KABUPATEN ROKAN HULU - -, Indrawati; Lestari, Rena; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Teacher performance is the level of success of a person or group in carrying out their duties and responsibilitiesas well as the ability to achieve goals and standars that have been set. This study aimed to analyze theperformance of teacher to their learning in subject biology in Madrasah Aliyah Kepenuhan. This research is adescriptive study. Population weres a biology teacher and all in class XI and XII Madrasah Aliyah KepenuhanRegency Rokan Hulu. Result showed the performance of the teachers were very good creteria with percentageof 74.39% and motivation of students get adequate criteria with percentage of 68.03%. This study showed theperformance of teachers was limited to studentsâ motivation. Because the teacherâs performance researchinstrument (IPKG 1) biology teacher did not use learning media.